Infinitely Many Small Energy Solutions to Schrödinger-Kirchhoff Type Problems Involving the Fractional <semantics>r(·)</semantics>-Laplacian in <semantics>RN</semantics> - Yun-Ho Kim (Fractal and Fractional, 2023)
This paper is concerned with the existence result of a sequence of infinitely many small energy solutions to the fractional <semantics>r(·)</semantics>-Laplacian equations of Kirchhoff–Schrödinger type with concave–convex nonlinearities when the convex term does not require the Ambrosetti–Rabinowitz condition. The aim of the present paper, under suitable assumptions on a nonlinear term, is to discuss the multiplicity result of non-trivial solutions by using the dual fountain theorem as the main tool.